PENGEMBANGAN POTENSI EKONOMI WILAYAH MENUJU DESA MANDIRI STUDI PADA SUMBER HARAPAN KABUPATEN SAMBAS - Sumar’in Sumar’in (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
The rural development paradigm that must be developed is aspirational development that prioritizes community participation and accommodates developing aspirations as the main factor in development planning and implementation. The independent village is the highest village status among the four other statuses, that independent village has an increasing level of community welfare and a low amount of poverty. The author in conducting field research (field research) with a qualitative descriptive analytical approach. The sample in this study is the village of Sumber Harapan. The conclusion of the study is that the Pontensi Desa Sumber Harapan that can be developed based on the analysis of the researcher includes 2 (two) aspects, namely the first aspect of weaving and the second aspect of agriculture and plantations.